TECHNOLOGICAL PROCESS MEDICINE - Salomov Ulugbek Abdikarim ugli; Elmurotova Dilnoza Bahtiyorovna; Meyliyev Laziz Orziqulovich (Scholar Express Journals, 2022)
The main subprocesses of the technological process and the tasks of medical technology are considered. It is also shown that medical technology belongs to the systemic areas in science and management of an interdisciplinary area in medicine
Keywords: Subprocess; medical technology; system; science